Stabilizing Effect of Magnesium Sulfate on Avian Infectious Bronchitis Virus Propagated in Chicken Embryo Kidney Cells - Coria, Manuel F. (Appl Microbiol, 1972)
The Beaudette strain of avian infectious bronchitis virus propagated in chicken embryo kidney cells is stabilized by exposure to 1 M MgSO(4) at 50 C for 80 min, at pH values ranging from 4 to 10.